Optimasi Formulasi Basis Krim melalui Variasi Perbandingan Jumlah Asam Stearat dan Trietanolamin - Suci Reski Utami; Fitri Amelia (Lembaga Yasin AlSys, 2025)
Cream is a commonly used cosmetic formulation known for its high stability, largely due to the presence of emulsifiers in its oil and water phases, such as stearic acid and triethanolamine. Emulsifiers play a crucial role in maintaining the physical stability of the formulation. This study aims to optimize cream formulations by varying the ratios of stearic acid to triethanolamine, evaluated based on smoothness and adhesiveness parameters. The tested ratio variations included 5/2; 5/2.5; 5/3; 5/3.5; 5/4; 10/2; 10/2.5; 10/3; 10/3.5; 10/4; 15/2; 15/2.5; 15/3; 15/3.5; 15/4; 20/2; 20/2.5; 20/3; 20/3.5; and 20/4, with each formulation tested in triplicate. The results indicated that several combinations met the required standards for smoothness and adhesiveness, including 5/2; 10/2.5; 10/3; 10/3.5; 10/4; 15/2; 15/2.5; 15/3; 15/3.5; 15/4; 20/2.5; and 20/3. Further analysis revealed a strong correlation between smoothness, adhesiveness, and viscosity, with viscosity being directly influenced by the amounts of stearic acid and triethanolamine in the formulation. This study produced a base cream formulation that may serve as a reference for further development, including active ingredient incorporation, quality testing, and evaluation of other physical properties.